Pendampingan Permainan Tradisional Ramah Disabilitas Bagi Pengguna Manfaat Disabilitas Netra PPSDSN Pendowo Kudus: Pengabdian - Syaffruddin Kuryanto, M.; Arsyad Fardani, M.; Hariyadi, Ahmad; Aditia Ismaya, Erik; Ari Pratiwi, Ika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
PPSDSN Pendowo Kudus faces challenges in the form of limited physical activity in people with visual disabilities, which has implications for low levels of physical fitness, physical condition, as well as the prevalence of obesity and limited physical abilities. As a response, this community service activity was designed with the aim of organizing physical activity coaching and balanced nutrition education. The method used is the utilization of traditional games adapted inclusively for blind disabilities, so that in addition to targeting physical health improvement towards an ideal body, it also functions as a medium for introducing traditions and culture. The main target is the provision of appropriate technology in the form of assistance in designing blind disability-friendly physical activities to improve fitness, along with the guidebook. The implementation of the activities succeeded in achieving the success indicators: the creation and implementation of blind disability-friendly games, the preparation of a physical activity guidebook, and the implementation of simulation and practice assistance which was greeted enthusiastically. The program evaluation resulted in three key conclusions: (1) the urgency of visually impaired friendly games, (2) the increased capability of orphanage teachers in designing and applying these games, and (3) the effective participation of people with visual disabilities without significant obstacles.